1994
DOI: 10.1203/00006450-199411000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Plasma Clotting, Fibrinolytic, and Kinin-Kallikrein System in Preterm Infants with Severe Idiopathic Respiratory Distress Syndrome

Abstract: We studied the activation pattern of clotting, fibrinolysis, and kinin-kallikrein during the first 5 d of life in 10 preterm infants with signs of severe idiopathic respiratory distress syndrome (IRDS) after birth (IRDS group) and in 12 healthy preterm infants (reference group). We found systemic activation of clotting, fibrinolysis, and kininkallikrein in the IRDS infants within 12 to 24 h of birth, represented by increased median thrombin-antithrombin I11 complex formation (90 ng/mL versus 10 ng/mL in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 9 publications
4
19
0
Order By: Relevance
“…Fibrin and its derivatives impair endothelial cell function, increase vascular permeability [23], promote chemotaxis [24], immobilize leukocytes within the fibrin network [25] and activate complement and kinin-kallikrein systems [26]. These effects support the hypothesis that fibrin deposition is an important determinant of lung injury.…”
Section: Discussionsupporting
confidence: 65%
“…Fibrin and its derivatives impair endothelial cell function, increase vascular permeability [23], promote chemotaxis [24], immobilize leukocytes within the fibrin network [25] and activate complement and kinin-kallikrein systems [26]. These effects support the hypothesis that fibrin deposition is an important determinant of lung injury.…”
Section: Discussionsupporting
confidence: 65%
“…Recently Brus et al reported that in RDS and chronic lung disease in preterm infants, systemic activation of inflammation could be found also (10,11).…”
mentioning
confidence: 99%
“…Indeed, the severity of RDS has been linked to the systemic concentration of thrombin-antithrombin III complex (3). In addition, preterm babies with RDS are more likely than their peers to have systemic activation of inflammation (4,5). We do not yet know if products of coagulation and inflammation co-occur in the blood of infants destined to develop bronchopulmonary dysplasia.…”
Section: Respiratory Distress Syndrome (Rds) In Preterm Newbornsmentioning
confidence: 99%